Marketplace Design Training for MSME Actors to Increase Online SMEs Sales Product in Temoroso, Guntur, Demak, Central Java - Sri Anik; Wasitowati (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Several community members in Temuroso village have created entrepreneurship with different types of businesses, such as fashion, culinary, trade, crafts, and food and beverage. Currently, the impact of the Covid-10 pandemic is still being felt by MSMEs in Temuroso, Guntur, Demak, including a decrease in turnover due to the decline in product sales and orders. The digital era is an exciting era for business and technology. The 4.0 era has had a shifting effect on marketing techniques. The benefits internet marketing offers mark this shift. In connection with this era, various efforts have been made for MSMEs in Temuroso, Guntur, Demak, including selling their products online. To better understand online sales and digital marketing as an effort to increase sales of MSME products online, MSME actors in Temuroso, Guntur, Demak, need to be given “Marketplace Design” training. The approach used in this marketplace design training is group-based, comprehensive, and competency-based. Moreover, activity methods in community service include socialization, increasing competence, implementing activities, and monitoring and evaluation. This training will be attended by around twenty MSMEs in Temoroso, Guntur, Demak. With this marketplace design training, MSMEs in Temoroso, Guntur, Demak will try to increase sales of their products online and increase their product postings on social media. This marketplace design training activity for MSMEs is beneficial for MSMEs in Temuroso, Guntur, Demak, in developing online sales of their products. Apart from that, this marketplace design training will really help MSMEs in Temuroso, Guntur, Demak to trade online.